American aesthetics : theory and practice - Gulick, Walter B., 1938-; Slater, Gary, 1983- (State University of New York Press, 2020)
"Although there are distinctly American artists-Walt Whitman, Herman Melville, Grandma Moses, Thomas Hart Benton, and Andy Warhol, for example-very little attention has been devoted to formulating any distinctively American characteristics of aesthetic judgment and practice. This volume takes a step in this direction, presenting an introductory essay on the possibility of such a distinctly American tradition, and a collection of essays exploring particular examples from a variety of angles. Some of the essays in this collection extend pragmatist and process insights about the important place aesthetics has in molding and assessing experience. Other essays examine the place of American aesthetics in relation to such particular forms of art as painting, literature, music, and film. Three essays attend to the aesthetic aspects of a flourishing life. In each of the essays, American aesthetics is understood to arise out of deeply felt personal, historical, and cultural backgrounds. Consequently, not only are such relatively abstract notions as harmony, fit, elegance, proportion, and the like involved in aesthetic judgment, but also religious, political, and social factors become embroiled in aesthetic discernment. Thus the ongoing pattern of American aesthetics is shown to be distinguishable from such other varieties of aesthetic thought as analytic aesthetics, New Criticism, and postmodern approaches to aesthetics"-- Provided by publisher.
Keywords: Aesthetics, American.; Esthétique américaine.; Aesthetics.; PHILOSOPHY.; Pragmatism.; Movements.; Aesthetics, American; Electronic books.